Are the basics of calculus necessary in Lithuanian gymnasium? - Apynis , Antanas; Šinkūnas, Juozas (Lietuvos matematikos rinkinys, 2021)
The article discusses the experience of Lithuania and some other European countries in respect of teaching the basics of calculus at secondary school.Attention is drawn to the fact that the basics of calculus is taught in several (2 to 4) levels in many European countries.A shift to a three-level teaching system as well as the arrangement of the state graduation examinations of mathematics according to the three-level curricula in Lithuanian gymnasia is suggested here.
Keywords: gymnasium; basics of calculus; curricula